Perspectives on the Future of Epidemiology: A Framework for Training. Issue 7 (31st January 2020) - Lau, Bryan; Duggal, Priya; Ehrhardt, Stephan; Armenian, Haroutune; Branas, Charles C; Colditz, Graham A; Fox, Matthew P; Hawes, Stephen E; He, Jiang; Hofman, Albert; Keyes, Katherine; Ko, Albert I; et al.
Abstract: Over the past century, the field of epidemiology has evolved and adapted to changing public health needs. Challenges include newly emerging public health concerns across broad and diverse content areas, new methods, and vast data sources. We recognize the need to engage and educate the next generation of epidemiologists and prepare them to tackle these issues of the 21st century. In this commentary, we suggest a skeleton framework upon which departments of epidemiology should build their curriculum. We propose domains that include applied epidemiology, biological and social determinants of health, communication, creativity and ability to collaborate and lead, statistical methods, and study design. We believe all students should gain skills across these domains to tackle the challenges posed to us. The aim is to train smart thinkers, not technicians, to embrace challenges and move the expanding field of epidemiology forward.